Transfer Accuracy of 3D-Printed Customized Devices in Digital Indirect Bonding: A Systematic Review and Meta-Analysis - Alessandra Campobasso; Giovanni Battista; Gianluigi Fiorillo; Giulia Caldara; Eleonora Lo Muzio; Domenico Ciavarella; Giorgio Gastaldi; Lorenzo Lo Muzio (International Journal of Dentistry)
Aim. To evaluate in vitro and in vivo the accuracy of 3D-printed customized transfer devices during indirect bonding technique (IBT). Methods. A search for articles published in the English language until April 2022 was carried out using PubMed, Web of Science, Scopus, and Google Scholar databases and by applying a specific search strategy for each database to identify all potentially relevant in vivo or in vitro studies. After the removal of duplicate articles and data extraction according to the participants-intervention-comparison-outcome-study design schema scheme, the methodological quality of the included studies was assessed using the Swedish Council on Technology Assessment in Health Care Criteria for Grading Assessed Studies. Results. The initial search identified 126 articles, 43 of which were selected by title and abstract. After full-text reading, 15 papers were selected for the qualitative analysis and seven studies for the quantitative analysis. The evidence quality for the selected studies was moderate. Conclusions. Except for the bucco-lingual direction, the 3D-printed customized devices have a transfer accuracy within the clinically acceptable limits established by the American Board of Orthodontics. Therefore, 3D-printed transfer devices may be considered an accurate method for bonding position during IBT, both in vitro and in vivo. Additional randomized clinical studies in vivo should be suggested.